Kontraktuele geregtigheid, goeie trou en die optrede van ’n kurator met betrekking tot onuitgevoerde kontrakte in die insolvensiereg - Stander, A. L. (Koers, 1996)
Contractual justice, good faith and the conduct of a trustee in relation to unexecuted contracts in the law of insolvencyRegarding unexecuted contracts and the important role they play in the law of insolvency, it is necessary to establish why a trustee is permitted to become a party to the contract between the insolvent and the third party without either party’s consent. This procedure mainly concerns the principle ofpublic policy as expressed in terms of good faith. Due to public policy and good faith, it is further necessary to create a healthy balance between the principles underlying the enforcement of contracts and those underlying the equal treatment of creditors o f the estate. To my mind the contracting third party can enforce the contract when its execution has reached the stage where the position of the concursus creditorum will not be affected. It is concluded that this stage is reached when no further performance is required of the insolvent estate. Under these circumstances it should be explicitly acknowledged that, on the basis of good faith, the third party has the right to insist on the performance of the contract. It is also essential that the decision of the trustee to enforce or to terminate the contract must be measured by the principle of good faith.